Bioavailable serum estradiol may alter radiation risk of postmenopausal breast cancer: a nested case-control study. (1st February 2018) - Grant, Eric J.; Cologne, John B.; Sharp, Gerald B.; Eguchi, Hidetaka; Stevens, Richard G.; Izumi, Shizue; Kim, Young-Min; Berrington de González, Amy; Ohishi, Waka; Nakachi, Kei
Abstract: Purpose: Ionizing radiation and high levels of circulating estradiol are known breast cancer carcinogens. We investigated the risk of first primary postmenopausal breast cancer in relation to the combined effects of whole-body ionizing radiation exposure and prediagnostic levels of postmenopausal sex hormones, particularly bioavailable estradiol (bE2 ). Materials and methods: A nested case-control study of 57 incident breast cancer cases matched with 110 controls among atomic bomb survivors. Joint effects of breast radiation dose and circulating levels of sex hormones were assessed using binary regression and path analysis. Results and conclusion: Radiation exposure, higher levels of bE2, testosterone and progesterone, and established reproductive risk factors were positively associated with postmenopausal breast cancer risk. A test for mediation of the effect of radiation via bE2 level suggested a small (14%) but significant mediation ( p  = 0.004). The estimated interaction between radiation and bE2 was large but not significant (interaction = 3.86; p  = 0.32). There is accumulating evidence that ionizing radiation not only damages DNA but also alters other organ systems. While caution is needed, some portion of the radiation risk of postmenopausal breast cancer appeared to be mediated through bE2 levels, which may be evidence for cancer risks due to both direct and indirect effects of radiation.